Advances in RNA cytosine-5 methylation: detection, regulatory mechanisms, biological functions and links to cancer - Chen Xue; Yalei Zhao; Lanjuan Li (2020)
Abstract As an important posttranscriptional modification of RNA, 5-methylcytosine (m 5 C) has attracted increasing interest recently, with accumulating evidence suggesting the involvement of RNA m 5 C modification in multiple cellular processes as well as tumorigenesis. Cooperatively, advances in m 5 C detection techniques have enabled transcriptome mapping of RNA methylation at single-nucleotide resolution, thus stimulating m 5 C-based investigations. In this review, we summarize currently available approaches for detecting m 5 C distribution in RNA as well as the advantages and disadvantages of these techniques. Moreover, we elucidate the regulatory mechanisms of RNA m 5 C modification by introducing the molecular structure, catalytic substrates, cellular distributions and biological functions of RNA m 5 C regulators. The functional consequences of m 5 C modification on mRNAs, tRNAs, rRNAs and other RNA species, including viral RNAs and vault RNAs, are also discussed. Finally, we review the role of RNA m 5 C modification in cancer pathogenesis and progression, in hopes of providing new insights into cancer treatment.